Students' perceptions and attitudes toward factors contributing to the high failure rate of first-year accounting students at a South African University - Olifant, T.; Cekiso, M. P.; Arendse, J.; Mandende , P.; Dieperink, M.; Jadezweni, J. (South African Journal of Higher Education, 2024)
The study explored what students perceived to be the contributing factors to the high failure rate in first-year Accounting. The study followed a quantitative research approach and method informed by a non-experimental survey design. A total number of 82 first-year Accounting students were purposively selected. The survey questionnaire that consisted of closed-ended questions was administered to the respondents. The quantitative data was analysed through SPSS to generate descriptive statistics and provide information about the internal consistency (called the Cronbach Alpha) of the questionnaire Likert scale items used to establish what factors contribute to the high failure rate among undergraduate first-year Accounting students. The findings revealed that many students were of the view that the instructional techniques used by lecturers did not demonstrate a practical application of Accounting to the students’ lives. Furthermore, the students indicated that Accounting lecturers’ language proficiency did impact their (i.e. the students’) achievement, as poor linguistic competency can result in a communication barrier and ultimately be a factor that influences the high failure rate in first-year Accounting students. An alarm-raising finding was that students indicated that although they enjoyed Accounting and gained personal satisfaction from doing it, they believed that they lacked motivation, which is a crucial influential contributor to high failure rate in the first-year Accounting students.